Effects of acidosis on neuronal voltage-gated sodium channels: Nav1.1 and Nav1.3 - Ghovanloo, Mohammad-Reza (Channels (Austin), 2018)
Voltage-gated sodium channels are key contributors to membrane excitability. These channels are expressed in a tissue-specific manner. Mutations and modulation of these channels underlie various physiological and pathophysiological manifestations. The effects of changes in extracellular pH on channel gating have been studied on several sodium channel subtypes. Among these, Nav1.5 is the most pH-sensitive channel, with Nav1.2 and Nav1.4 being mostly pH-resistant channels. However, pH effects have not been characterized on other sodium channel subtypes. In this study, we sought to determine whether Nav1.1 and Nav1.3 display resistance or sensitivity to changes in extracellular pH. These two sodium channel subtypes are predominantly found in inhibitory neurons. The expression of these channels highly depends on age and the developmental stage of neurons, with Nav1.3 being found mostly in neonatal neurons, and Nav1.1 being found in adult neurons. Our present results indicate that, during extracellular acidosis, both channels show a depolarization in the voltage-dependence of activation and moderate reduction in current density. Voltage-dependence of steady-state fast inactivation and recovery from fast inactivation were unchanged. We conclude that Nav1.1 and Nav1.3 have similar pH-sensitivities.